Programed learning a comparative evaluation of student performance variables under combinations of conventional and automated instruction - Flint, Lanning L.; Hatch, Richard S. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1962)
Student performance variables under automated, conventional, and a combination of automated and conventional conditions of instruction were investigated. Recommendations for the integration of programed material into the classroom were sought. Three groups of junior college students were used in the experiment. The groups were chosen at random. One group had twice as much instruction time per week and this instruction was evenly divided between lectures and programed material. Another group had only lectures. The third group had only programed material. Criterion tests, psychological tests, and an interview were used for evaluating achievement. The group that received lectures and programed instruction showed the greatest achievement. The other two groups showed about equal achievement. Differences in progress rates were attributed to personality differences. There was no evidence of time saving with the programed materials. Test results were presented in two tables. A bibliography and an appendix of student attitudes toward teaching machines were included.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Bibliographies; Programed Instruction; Programed Instructional Materials; Student Attitudes; California (Goleta)